Establishment and validation of a rodent model of endometriosis to evaluate the effect of new therapeutic strategies - Rana Assaly; Sandrine Compagnie; Laurine Allimonnier; Manon Bracconi; Francois Giuliano; Delphine Behr-Roussel (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2022)
Objectives: Endometriosis is a common disease that affects about 10% - 15% of women in their reproductive years worldwide with no curative treatment. The most common symptom of endometriosis is debilitating pelvic/abdominal pain. Current therapeutic options have limited insight into the disease mechanism and include drugs and/or surgery, which may be ineffective over the long term with unwanted side effects. We aimed at establishing a translational rodent endometriosis model that can be used to identify novel therapies. The validity of the model was confirmed by investigating the effect of the clinically-used GnRH agonist, leuprolide. Methods: Endometriosis was induced by a surgical procedure in adult non-pregnant female Sprague Dawley rats in the diestrus or estrus stage (cycle determination by vaginal smear). One group of rats received a subcutaneous injection of leuprolide at 1mg/kg, every 4 weeks. Following the treatment period, we performed a direct assessment of the endometriosis-induced abdominal pain using the Von-Frey method and spontaneous pain using the abdominal licking test. Then, the lesions were excised and measured. Results: Abdominal pain threshold was decreased by more than 2 fold in rats with surgically-induced endometriosis compared to sham rats. Leuprolide treatment significantly increased the threshold force required to elicit a behavioral withdrawal response in rats suffering from endometriosis. The observed pelvic floor mechanical hyperalgesia has not been correlated to the growth of endometriosis lesions. The hormonal cycle at the surgery induction influenced the endometriosis lesions growth. Leuprolide significantly inhibited the growth of endometriosis-like lesions. Conclusions: we have established, based on previously reported rodent models, a model of endometriosis-associated pain that responds to clinically active drugs and can, therefore, be used to identify novel therapies and investigate some of the pathophysiological mechanisms involved in endometriosis.